(3EQTGO Phi GdYQaGf deG ddYeQ ef GdRjGOI hGdfbUGfs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3GdMeO def Ndb GddhM hGdbde CeG HYO agPg aQGFO jJjeI hahGFO KejfI hYbhO LhGgQ eVjI GdebOeI ai EKHGJ MbjbI GdbOQ s
(3BNQgG (B:s
(3bGd eDdag GdMbjQ eQYi GHf jhSa GdMfHdi dNUJ gPg GdQSGdI ef cJGHi HgLI GdfGXQjf hcJGHi CQhGM GdCTHGM ai jhei GdSHJ hGdCMO ai GdYTQjf ef QeVGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdhGQO MOjKkG s
Keywords: (3Gdabg GdMfHdjs